A qualitative study exploring the social and environmental context of recently acquired HIV infection among men who have sex with men in South-East England. Issue 8 (28th August 2017) - Gourlay, Annabelle; Fox, Julie; Gafos, Mitzy; Fidler, Sarah; Nwokolo, Nneka; Clarke, Amanda; Gilson, Richard; Orkin, Chloe; Collins, Simon; Porter, Kholoud; Hart, Graham
Abstract : Objectives: A key UK public health priority is to reduce HIV incidence among gay and other men who have sex with men (MSM). This study aimed to explore the social and environmental context in which new HIV infections occurred among MSM in London and Brighton in 2015. Design: A qualitative descriptive study, comprising in-depth interviews, was carried out as a substudy to the UK Register of HIV Seroconverters cohort: an observational cohort of individuals whose date of HIV seroconversion was well estimated. An inductive thematic analysis was conducted in NVivo, guided by a socio-ecological framework. Setting: Participants were recruited from six HIV clinics in London and Brighton. Fieldwork was conducted between January and April 2015. Participants: All MSM eligible for the UK Register Seroconverter cohort (an HIV-positive antibody test result within 12 months of their last documented HIV-negative test or other laboratory evidence of HIV seroconversion) diagnosed within the past 12 months and aged ≥18 were eligible for the qualitative substudy. 21 MSM participated, aged 22–61 years and predominantly white. Results: A complex interplay of factors, operating at different levels, influenced risk behaviours and HIV acquisition. Participants saw risk as multi-factorial, but the relative importance of factors varied for each person. Individual psycho-social factors, including personal history, recent life stressors and mental health, enhanced vulnerability towards higher risk situations, while features of the social environment, such as chemsex and social media, and prevalent community beliefs regarding treatment and HIV normalisation, encouraged risk taking. Conclusions: Recently acquired HIV infection among MSM reflects a complex web of factors operating at different levels. These findings point to the need for multi-level interventions to reduce the risk of HIV acquisition among high-risk MSM in the UK and similar settings.